Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Tram coming up tramway to top of Lookout Mountain; Chattanooga and Tennessee River in background Power/telephone poles along tramway route